Eco—Motricity: An Epistemic Turn to Re-Thinking Physical Education in Chile - Toro-Arevalo, S (Universidad de Alicante, 2021)
The main purpose of this paper is to stress the epistemic and ontological proposal of the physical education. Subsequently, and using a critical reflection approach in the context of climate change and environmental crisis, the Eco-motricity proposal is presented, which represent an epistemic turn into the discipline and, in consequence, a didactic which consider the construction of a new ethic and relationships among individuals. Finally, challenges, new pathways and questions in the physical education research and the practices in the school are proposed. © 2021. Faculty of Education. University of Alicante. All Rights Reserved.